2008
DOI: 10.1002/pssb.200879661
|View full text |Cite
|
Sign up to set email alerts
|

Stability of carbon nanotubes to laser irradiation probed by Raman spectroscopy

Abstract: We report on a systematic study of the influence of laser irradiation on the Raman spectra of HiPco‐produced single‐wall CNTs. Specifically, we have examined the Raman response of bundled CNTs to: i) laser power density; ii) exposure time and iii) photon energy (1.96 and 2.33 eV). Our results show that irreversible destruction of CNTs in the bundles can occur at even low laser power density (0.15 kW/cm2). The tubes with smaller diameters are influenced first and the rate of CNT destruction increases with photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…It is consistent with the Raman signal attenuation at 5-9 GPa reported for bundled DWCNTs at hydrostatic conditions [6,7]. The inner-tube RBMs survive substantially higher pressure (about 19 GPa for 532 nm excitation) which is almost twice the collapse pressure (10-12 GPa) estimated for DWNCTs in our system (effective radius of 0.52 nm) according to Gadagkar et al [1] and Yang et al [2].…”
Section: Resultssupporting
confidence: 91%
“…It is consistent with the Raman signal attenuation at 5-9 GPa reported for bundled DWCNTs at hydrostatic conditions [6,7]. The inner-tube RBMs survive substantially higher pressure (about 19 GPa for 532 nm excitation) which is almost twice the collapse pressure (10-12 GPa) estimated for DWNCTs in our system (effective radius of 0.52 nm) according to Gadagkar et al [1] and Yang et al [2].…”
Section: Resultssupporting
confidence: 91%
“…The authors conclude that intense laser irradiation can lead to the loss of impurities and results in a purified CNT sample. In a study by Raman spectroscopy on the stability of carbon nanotubes to laser irradiation, Olevik et al [29] mention the particular sensitivity of CNT bundle materials to overheating due to inefficient cooling in this system compared to invividual CNTs and show that irreversible destruction of CNTs in the bundles can occur at even low laser power density (0.15 kW/cm 2 ). From the above reported results, it appears that laser induced effects are very important to consider for the analysis of the Raman spectrum of CNTs.…”
Section: Thermal Effects Caused By Incident Laser Irradiationmentioning
confidence: 99%
“…Measurements of RBM (radial breath modes) spectra from single-walled (SW) CNT irradiated in air revealed that a preferential destruction of SWCNTs occurs for moderately large laser intensities. There is some controversy if the irradiation of SWCNT bundles destructs preferentially thinner 22,23 or metallic tubes. 24 It is also possible to take advantage of the damage produced by irradiation in air with very high intensities to unzip CNTs generating graphene nanoribbons.…”
Section: Introductionmentioning
confidence: 99%
“…This technique provides information on both the crystalline structure and the temperature of the irradiated CNTs during the laser treatment. Previous works on laser irradiation were usually performed in air, mostly in exposed films of CNT bundles [19][20][21][22][23][24] or in films covered with a quartz plate to reduce air exposure. 25 Results indicate that irradiation in air can affect CNTs in various forms.…”
Section: Introductionmentioning
confidence: 99%